2019
DOI: 10.3168/jds.2018-15784
|View full text |Cite
|
Sign up to set email alerts
|

Pasture allowance, duration, and stage of lactation—Effects on early and total lactation animal performance

Abstract: Pasture availability in early spring can be limited due to climatic effects on grass production, increasing the likelihood of feed deficits in early lactation of springcalving pasture-based systems. We hypothesized that restricting pasture allowance (PA) when animals are at peak milk production will have more negative implications on milk production compared with restricting animals before this period. A total of 105 cows were assigned to 1 of 7 grazing treatments from March 14 to October 31, 2016 (33 wk). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Our values exceed the annual yields of Mendoza et al ( 2018) [20], Rojas et al ( 2017) [27], [6] and Annicchiarico and Tomasoni (2010) [29], probably due to the establishment of these pastures associated for several decades -related to age, climatic conditions [18,19] that occur in the inter-Andean valley of the northern highlands of Peru, which is characterised by two well-defined climatic seasons during the year: rainfall and low water or drought; conditions that influence the productive behaviour of this forage association. From another perspective, when considering the time of year and the rainy season, the evaluated forage floor has a higher biomass accumulated per day, but there is no difference per cut.…”
Section: Productive Performancecontrasting
confidence: 69%
See 2 more Smart Citations
“…Our values exceed the annual yields of Mendoza et al ( 2018) [20], Rojas et al ( 2017) [27], [6] and Annicchiarico and Tomasoni (2010) [29], probably due to the establishment of these pastures associated for several decades -related to age, climatic conditions [18,19] that occur in the inter-Andean valley of the northern highlands of Peru, which is characterised by two well-defined climatic seasons during the year: rainfall and low water or drought; conditions that influence the productive behaviour of this forage association. From another perspective, when considering the time of year and the rainy season, the evaluated forage floor has a higher biomass accumulated per day, but there is no difference per cut.…”
Section: Productive Performancecontrasting
confidence: 69%
“…From another perspective, when considering the time of year and the rainy season, the evaluated forage floor has a higher biomass accumulated per day, but there is no difference per cut. It should be considered that in rainy conditions, both the yield in kg DM ha −1 cut-1 and kg DM ha −1 year-1 was higher than the results referred by Claffey et al (2019) [18]; Tozer et al (2014) [19] and Mendoza et al (2018) [20], so in the rainy season the biomass productivity was higher than in the dry season by 18.74 %, a period that lasts about six months, adding that the areas under study, during the dry season, were irrigated fortnightly by flooding, but rainfall water affects productivity.…”
Section: Productive Performancementioning
confidence: 56%
See 1 more Smart Citation
“…Grazing cows fed very different planes of nutrition on a short-term basis may not show as substantial difference in performance (Burke et al, 2010;Claffey et al, 2019). However, where grazing cows have been fed different planes of nutrition in early lactation for longer periods (2 vs. 6 wk), performance differences are evident (Kennedy et al, 2015;Claffey et al, 2019). Furthermore, some of these performance differences extend beyond the time of nutritional treatment.…”
Section: Drymentioning
confidence: 99%
“…Dairy cows diets, particularly during early lactation, can have a significant impact on animal performance (Kennedy et al, 2007). Restricting DMI during early lactation has been shown to have a negative impact on subsequent milk production (Claffey et al, 2019b). Claffey et al (2020a) reported an increase in milk production of 0.38 kg milk/cow/day per kg DM increase in DHA.…”
Section: Introductionmentioning
confidence: 99%